Anti-atherosclerotic effects of Camellia chrysantha and Gynostemma pentaphyllum extracts mixture - Hong Hanh Nguyen; Ngan Hoang Nguyen; Tu Thi Thanh Nguyen (Shahrekord University of Medical Sciences, 2023)
Introduction: The combination Camellia chrysantha and Gynostemma pentaphyllum is used in Vietnam against hyperlipidemia. This study aims to evaluate the effects of the extract mixture of C. chrysantha and G. pentaphyllum in the atherosclerosis-induced rat model. Methods: Rats were administered with the extract mixture of C. chrysantha and G. pentaphyllum daily (7 and 14 g/kg/day) for 8 weeks upon the start of the study while they were simultaneously put on an atherosclerosis-induced diet. Blood samples were taken to examine the blood lipid indicators of the rats in the beginning, after 4 and 8 weeks of the study, respectively. After 8 weeks of treatment, the rats' livers were removed to assess their overall health and the atherosclerosis patterns of their abdominal arteries. Results: The mixture of leaf extracts of C. chrysantha and G. pentaphyllum in the doses of 7 and 14 g/kg/day reduced blood lipid indices, including triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) levels and the atherogenic index (AI). Furthermore, this mixture also increased the levels of high-density lipoprotein cholesterol (HDL-C) in the blood, decreased the incidence of liver fat, and prevented the development of atherosclerotic lesions in the abdominal aorta in the rats. Conclusion: These results indicate that a mixture of C. chrysantha and G. pentaphyllum has a potential in preventing and treating atherosclerosis